2017
DOI: 10.13168/cs.2017.0037
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Mechanical Behavior of a Minicomposite Based on Grey Verhulst Models

Yiqiang Wang

Abstract: The tensile behavior of a C/SiC minicomposite fabricated by chemical vapor infiltration was examined and the associated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Comparison of σc,el with the compressive strength of the bead core σc,c of approximately 2.1 N/mm 2 [14] confirms that that the material is indeed weaker in tension. It is noted that the limiting elastic strains found for the bead cores in the present study are approximately equivalent to those found for ceramic matrix minicomposites employed in aeronautical applications [35,36].…”
Section: Determination Of Mechanical Propertiessupporting
confidence: 70%
See 1 more Smart Citation
“…Comparison of σc,el with the compressive strength of the bead core σc,c of approximately 2.1 N/mm 2 [14] confirms that that the material is indeed weaker in tension. It is noted that the limiting elastic strains found for the bead cores in the present study are approximately equivalent to those found for ceramic matrix minicomposites employed in aeronautical applications [35,36].…”
Section: Determination Of Mechanical Propertiessupporting
confidence: 70%
“…Although it can be seen that there exists a degree of variability between their flexural responses, after a certain amount of deformation (δ = 0.5-0.6 mm), the material undergoes some softening with the flexural rigidity of the specimens reducing up until failure. From a micromechanical perspective, analogies can be drawn from analyses of fibre-ceramic composites in tension [35,36], whereby the constituent materials of the glass-polymer composite initially undergo elastic deformation up to a level of strain whereupon damage at the microscale initiates that manifests itself at the macroscale as an overall loss of stiffness; the damage mechanisms include cracking of the polymer matrix and interfacial debonding from the particles [32,33]. Damage continues to propagate through the specimen with increasing load until failure occurs, with a large diagonal crack such as that shown in Figure 4a visible.…”
Section: Flexural Testing Of Small-scale Panel Sectionsmentioning
confidence: 99%
“…The probability of the corresponding state is determined according to (21), and the predicted value of the residual error can be calculated.…”
Section: The Mgvm Model Based On Markov Optimizationmentioning
confidence: 99%
“…The grey Verhulst model based on PSO algorithm is adopted to discuss the relationship between CO 2 emissions and economy by Wang and Li [20]. The grey Verhulst model and inverse Verhulst model are established to predict the mechanical behavior of a minicomposite by Wang et al [21]. An optimal grey Verhulst model is proposed to predict the concentration of nitrogen in seawater by Hu et al [22].…”
Section: Introductionmentioning
confidence: 99%
“…Many in situ monitoring techniques, including acoustic emission (AE), X-ray microtomography, and acousto-ultrasonics (AU), have been used to detect and reveal internal damage evolution mechanisms in minicomposites [ 9 , 10 , 11 , 12 ]. Under tensile load, the damages in the minicomposites can be divided into different stages and the damage stages are affected by the fiber type and interphases [ 13 , 14 , 15 , 16 ]. Heat-treatment at elevated temperature causes damages in the fiber and interphase, leading to the degradation of tensile performance of mini-CMCs [ 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%